Obstetric Management of Delayed-Interval Delivery - Maria Inês Raposo; Mariana Cardoso; Mariana Ormonde; Sarah Stokreef; Laura Correia; Andrea Pereira (Elsevier, 2017)
The delayed-interval delivery is a rare, flexible and complex procedure. In light of these facts, there is no consensus on the best approach to achieve it successfully. This case report is of an asynchronous delivery, in a twin pregnancy, with a 32-day interval between births of siblings. Our obstetric management at a critical gestational age improved the outcome of the second newborn. The probability of success of delayed-interval delivery depends on the proper selection of the candidates, the appropriate active management and the continuous monitoring for early detection of complications.